Invasive ductal breast cancer within a malignant phyllodes tumor: case report and assessment of clonality - Macher-Göppinger, Stephan; Marmé, Frederik; Goeppert, Benjamin; Penzel, Roland; Schirmacher, Peter; Sinn, Peter; Aulmann, Sebastian (Human pathology, 2010)
Invasive carcinomas arising within fibroepithelial tumors represent an uncommon manifestation of breast cancer. We report the case of a 70-year-old woman who underwent mastectomy for a malignant phyllodes tumor measuring 6 cm.